Skill Mismatch as Constraint to Entrepreneurship in the Leather Sector of Bangladesh: A Conceptual Study (Social Science Review, 2023)
Promoting entrepreneurship is a key approach to reducing youth unemployment and enhancing economic development. This paper aims to explore skill mismatch as a constraint to entrepreneurship in the leather sector of Bangladesh. The paper is a conceptual study and follows the worldview of critical realism. This study used one-to-one interviews and a survey based on a non-probability sampling procedure to supplement the conceptual analysis. The empirical findings were considered complementary evidence to the conceptual discussion. The study was designed to explore the issues related to skill mismatch through a conceptual analysis instead of aiming to make generalizable statistical inferences. The paper had two major findings. Firstly, the ability to develop ‘political connections’ is considered an important skill that entrepreneurs look for in their business partners and managers, especially at the early stage of business capital formation. Other forms of skills mismatch impose a high amount of cost on the entrepreneurs and function as an entry barrier to entrepreneurship. Secondly, entrepreneurs are not well incentivized to invest in training and up-skilling their workers due to the high risk associated with such investments.Social Science Review, Vol. 39(1), June 2022 Page 103-123